Application of Molecular Emissions in Laser-Induced Breakdown Spectroscopy: A Review - Xu, Fanghao; Ma, Shixiang; Zhao, Chunjiang; Dong, Daming (Frontiers in Physics, 2022)
Laser-induced breakdown spectroscopy (LIBS) with advantages of rapid, in situ and little sample pretreatment has been used in various fields. However, LIBS technology remains challenging in the detection of halogens, isotopes, and samples with similar elements. Therefore, molecular emission was proposed to improve the detection ability of LIBS. In this review, we introduced molecular emissions formed by organic elements, oxidable elements, and halogens. Then, Molecular emission in different experiment parameters, such as the acquisition window, laser characters (laser energy, laser pulse, and pulse duration) and ambient atmospheres, were discussed. In the end, we highlight the application of molecular emissions on element content determination, material types classification, and combustion and explosion processes monitoring.